Lifestyle Ehealth and Mhealth Interventions for Children and Adolescents: Systematic Umbrella Review and Meta-Meta-Analysis - Suarez-Reyes, M (JMIR PUBLICATIONS, INC, 2025)
Background: eHealth and mobile health (mHealth) interventions are promising in promoting healthy behaviors among children and adolescents. Objective: This systematic umbrella review and meta-meta-analysis aimed to evaluate the effectiveness of eHealth and mHealth interventions in promoting healthy behaviors among children and adolescents. Methods: Nine databases were searched for systematic reviews and meta-analyses of randomized controlled trials of eHealth and mHealth interventions targeting physical activity, sedentary behavior, sleep, and dietary outcomes in children and adolescents aged below 18 years. Screening, data extraction, and all assessments were completed by 2 reviewers. Study quality was assessed using the AMSTAR-2 (A Measurement Tool to Assess Systematic Reviews-2) checklist, and meta-analyses were conducted to combine effect sizes using random effects models. Subgroup analyses examined participant and intervention characteristics. Results: A total of 25 systematic reviews comprising 440 randomized controlled trialsand 133,501 participants, mostly involving healthy children and adolescents (n=18, 72%) or those who were overweight or with obesity (n=4, 16%), were included. Interventions mostly included active video games or serious games (n=8, 32%), various mHealth interventions (n=6, 24%), various eHealth interventions (n=5, 20%), combined eHealth and mHealth interventions (n=4, 16%), wearables (n=1, 4%), and computer-based interventions (n=1, 4%). Most studies (n=18, 72%) had critically low AMSTAR-2 scores. Meta-analyses based on standardized mean difference (SMD) showed significant effects (all P<.05) for moderateto vigorous physical activity (SMD 0.18, 95%CI 0.09-0.27), total physical activity (SMD 0.24, 95%CI 0.13-0.35), fat intake(SMD 0.10, 95%CI 0.02-0.18), fruit and vegetable intake (SMD 0.11, 95% CI 0.00-0.22), BMI (SMD 0.19, 95% CI 0.11-0.27), and body weight (SMD 0.15, 95% CI 0.01-0.30). No effects were found for sedentary behavior (SMD 0.12, 95% CI-0.11 to 0.35) or sleep (SMD 0.27, 95% CI-0.09 to 0.63). Shorter interventions (lasting <8 weeks) had a greater effect on moderate to vigorous physical activity than longer interventions (lasting >= 8 weeks), while longer interventions (lasting >= 12 weeks) had a greater effect on BMI compared with shorter interventions. Conclusions: eHealth and mHealth interventions offer modest but meaningful improvements in physical activity, diet, and weight management in children and adolescents, with important implications for integrating digital tools into health promotion strategies.